(untitled) (Journal of Fatima Jinnah Medical University, 2020)
Non-alcoholic fatty liver disease (NAFLD) includes simple fatty change, hepatitis and cirrhosis. Patients with non-alcoholic fatty liver disease are at increased risk of arteriosclerosis, metabolic syndrome, cardiovascular and psychiatric disorders. Depressive disorders are among the prevalent psychiatric illnesses and pose public health problem. Depression is associated with poor outcome in the treatment of non-alcoholic fatty liver disease especially with lifestyle modifications. The aim of this study is to determine the frequency of depression in patients with NAFLD. Patients and Methods: Total of 170 newly diagnosed patients with non-alcoholic fatty liver disease based on ultrasound were included in the study. The frequency of depression was calculated using the Patient Health Questionnaire (PHQ-9) scale and other causes of depression particularly chronic diseases other than nonalcoholic steatohepatitis (NASH) and family history of psychiatric illness were excluded. A score of > 20 was suggestive of severe depression. Results: Average age was 39.8 ± 8.8 years. 109 patients (64.1%) were male. Of this population, 41 patients (24.1%) suffered from depression according to depression scale PHQ-9 score. There were no effects of age, gender, socioeconomic status on depression in patients with fatty liver disease. Conclusion: It is concluded that depression is more frequent in patients with non-alcoholic fatty liver disease.